2011
DOI: 10.3168/jds.2010-4063
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analyses of protein yield in dairy cows applying random regression models with time-dependent and temperature x humidity-dependent covariates

Abstract: Data used in the present study included 1,095,980 first-lactation test-day records for protein yield of 154,880 Holstein cows housed on 196 large-scale dairy farms in Germany. Data were recorded between 2002 and 2009 and merged with meteorological data from public weather stations. The maximum distance between each farm and its corresponding weather station was 50 km. Hourly temperature-humidity indexes (THI) were calculated using the mean of hourly measurements of dry bulb temperature and relative humidity. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
82
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(93 citation statements)
references
References 30 publications
10
82
0
1
Order By: Relevance
“…As most of the heritability estimates were higher at lower THI values (Table 3), the greatest responses to selection can be expected for the thermal comfort zone. Brügemann et al (2011) have reported similar results for German Holstein cows and Bohlouli et al (2013) for Iranian Holstein cows. Brügemann et al (2011) stated that the effect of heat stress can suppress the full expression of the genetic potential of animals.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…As most of the heritability estimates were higher at lower THI values (Table 3), the greatest responses to selection can be expected for the thermal comfort zone. Brügemann et al (2011) have reported similar results for German Holstein cows and Bohlouli et al (2013) for Iranian Holstein cows. Brügemann et al (2011) stated that the effect of heat stress can suppress the full expression of the genetic potential of animals.…”
Section: Discussionsupporting
confidence: 70%
“…The heritability estimates obtained for the different combinations of DIM and THI indicate that the response to selection can vary as a function of both DIM and THI, a fact also reported in other studies (Aguilar et al, 2009;Brügemann et al, 2011;Bohlouli et al, 2013). As most of the heritability estimates were higher at lower THI values (Table 3), the greatest responses to selection can be expected for the thermal comfort zone.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…While the effects of heat stress on dairy cows has been well-documented in tropical and subtropical regions (e.g. West et al, 2003;Dikmen and Hansen, 2009), a growing number of studies has also reported associations between THI and milk traits in temperate regions where tolerance to heat stress is lower (Bruegemann et al, 2011;Hammami et al, 2013;Dunn et al, 2014). Moreover, temperatures are predicted to increase over the 21st century in southern Scotland, especially in summer, with an expected mean daily maximum temperature increase of 4.3°C by the 2080s with a very slight reduction (0% to 5%) in humidity (Jenkins et al, 2009).…”
mentioning
confidence: 99%
“…These validation studies were carried out primarily in (sub) tropical and arid regions, and they were carried out on lessproductive dairy cows rather than those generally reared nowadays (Zimbelman et al, 2009), especially in temperate regions. On the other hand, Brügemann et al (2011) identified a lower daily average THI value of 60 as the threshold for declining milk protein content in German Holstein cows. Hammami et al (2013) proposed a daily average THI value of 62 as a new threshold for Western European Holstein cows, above which milk yield was found to decline with 0.164 kg/ day per cow.…”
Section: Introductionmentioning
confidence: 99%